Massilia timonae bacteremia: An unusual pathogen of septic abortion - Gawahir A. Ali (14777260) (2022)
Massilia timonae infections in humans have rarely been reported. To the best of our knowledge, M. timonae has not been previously recognized as a causative agent of obstetric or gynecological infections. Timely identification of this unusual pathogen and the use of targeted antimicrobial therapy are crucial to avoid consequences and treatment failure. Other Information Published in: IDCases License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.idcr.2022.e01592